BET 1: is long-term Rivaroxaban superior to Warfarin in pulmonary embolism?. Issue 11 (20th October 2015) - Morgan, Christopher; Body, Richard
Abstract : A short cut review was carried out to establish whether Rivaroxaban is superior to warfarin in the management of pulmonary embolism. Three studies were directly relevant to the question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. The clinical bottom line is that Rivaroxaban is a promising alternative to warfarin in the management of pulmonary embolism.